Interest Rate Spread on Bank Profitability: The Case of Ghanaian Banks - Owusu-Antwi, George; Banerjee, Rachna; Antwi, James (Journal of Accounting, Business and Finance Research, 2017)
The banking sector in Ghana plays a dominant role in the financial sector, particularly with respect to mobilization of savings and the provision of credit. An analysis of bank interest rate spreads is therefore central to the understanding of the financial intermediation process and the macroeconomic environment in which banks operate. This paper is motivated by the fact that although Ghana’s financial sector was liberalized in the early 1990s to allow for market determination of interest rates, concerns about high interest rate spreads have persisted and attracted a lot of debate in both public and policy forums. The purpose of the study is to empirically investigate the interest rate spread on banks profitability in Ghana using average annual observation data from1992–2015 to include 28 commercial banks. Ordinary least square was used to estimate the regression coefficients. The empirical results show that bank-specific factors play a significant role in the determination of interest rate spreads in the Ghana’s banking sector. All the bank specific variables were found to be significant except Total Assets (TA). Among the macroeconomic variables, inflation was found to be significant whereas GDP growth rate was insignificant. The role of the global financial institutions is changing and so are the banks operating in Ghana. The banking sector should explore new paths that will enable them to take advantage of the government’s policy of making the “private sector the engine of growth” to market their products.